2019
DOI: 10.15252/msb.20188777
|View full text |Cite
|
Sign up to set email alerts
|

Digitalizing heterologous gene expression in Gram‐negative bacteria with a portable ON/OFF module

Abstract: While prokaryotic promoters controlled by signal‐responding regulators typically display a range of input/output ratios when exposed to cognate inducers, virtually no naturally occurring cases are known to have an OFF state of zero transcription—as ideally needed for synthetic circuits. To overcome this problem, we have modelled and implemented a simple digitalizer module that completely suppresses the basal level of otherwise strong promoters in such a way that expression in the absence of induction is entire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 82 publications
(101 reference statements)
0
34
0
Order By: Relevance
“…3A). Although this level is not too high (it remains within the same order of magnitude than the baseline expression), it has to be taken into account when expression of toxic proteins or coupling with other devices are pursued (27). A second aspect of the results shown in Fig.…”
Section: The Effect Of Formatting Alks/palkb In the Performance Of Thmentioning
confidence: 98%
“…3A). Although this level is not too high (it remains within the same order of magnitude than the baseline expression), it has to be taken into account when expression of toxic proteins or coupling with other devices are pursued (27). A second aspect of the results shown in Fig.…”
Section: The Effect Of Formatting Alks/palkb In the Performance Of Thmentioning
confidence: 98%
“…Furthermore, rrn operons have demonstrated a strong preference for biosynthetic gene cluster integration in P. putida , due to stable integration and strong expression by the native promoters (Domröse et al 2019 ). Finally, it was recently demonstrated that fine-tuning of metabolic pathways via targeted proteolysis enables a new control layer of engineered pathways (Calles et al 2019 ; Volke et al 2020b ) .…”
Section: Recent Advances In Genetic Engineeringmentioning
confidence: 99%
“…The radius described by the partially formed monomers is r 1 and r 2 respectively. In this scenario, the spheres are then described by: (9) and (x − ∆x) 2 + y 2 + z 2 ≤ r 2 2…”
Section: Calculation Of Overlapping Spheresmentioning
confidence: 99%
“…The development of complex mathematical modelling techniques [4,5], along with the advances in DNA synthesis and assembly [6], allows for the making of new-to-Nature networks of regulatory proteins-the so-called genetic circuits-with increasing information processing abilities. Relatively simple models of computation, like combinatorial [7] and sequential logic [8], have been successfully implemented in organisms such as bacteria [9], yeasts [10] or even mammalian cells [11]. Examples of these genetic circuits include logic gates [12,13], multiplexers [14], half-adders [15], counters [16] and memories [17]-even more complex processes such as analogue [18,19] and distributed computations [20,21,22].…”
Section: Introductionmentioning
confidence: 99%